Lipid bubbles combined with low-intensity ultrasound enhance the intratumoral accumulation and antitumor effect of pegylated liposomal doxorubicin in vivo - Inoru Yokoe; Daiki Omata; Johan Unga; Ryo Suzuki; Kazuo Maruyama; Yoshiharu Okamoto; Tomohiro Osaki (Taylor & Francis Group, 2021)
Pegylated liposomal doxorubicin (PLD) is a representative nanomedicine that has improved tumor selectivity and safety profile. However, the therapeutic superiority of PLD over conventional doxorubicin has been reported to be insignificant in clinical medicine. Combination treatment with microbubbles and ultrasound (US) is a promising strategy for enhancing the antitumor effects of chemotherapeutics by improving drug delivery. Recently, several preclinical studies have shown the drug delivery potential of lipid bubbles (LBs), newly developed monolayer microbubbles, in combination with low-intensity US (LIUS). This study aimed to elucidate whether the combined use of LBs and LIUS enhanced the intratumoral accumulation and antitumor effect of PLD in syngeneic mouse tumor models. Contrast-enhanced US imaging using LBs showed a significant decrease in contrast enhancement after LIUS, indicating that LIUS exposure induced the destruction of LBs in the tumor tissue. A quantitative evaluation revealed that the combined use of LBs and LIUS improved the intratumoral accumulation of PLD. Furthermore, tumor growth was inhibited by combined treatment with PLD, LBs, and LIUS. Therefore, the combined use of LBs and LIUS enhanced the antitumor effect of PLD by increasing its accumulation in the tumor tissue. In conclusion, the present study provides important evidence that the combination of LBs and LIUS is an effective method for enhancing the intratumoral delivery and antitumor effect of PLD in vivo.